PENGARUH KOMPETENSI PETANI, TEKNOLOGI PERTANIAN, DAN PENYULUHAN TERHADAP KINEJA PETANI KAKAO YANG DIMEDIASI OLEH MOTIVASI KERJA (Studi Pada Petani kakao di Kabupaten Jayapura Papua) - Tangkelayuk, Herman (Agros Journal of Agriculture Science, 2024)
The use of agricultural technology supported by competency and extension is expected to increase the motivation of cocoa farmers in the Jayapura district and have an impact on improving the welfare of farmers. In this research, we will examine how competence, agricultural technology, and extension impact performance, which is mediated by motivation. Questionnaires were distributed to 210 cocoa farmers in Jayapura district, and the data collected was analyzed using covariance-based SEM (CB-SEM). The results show that competence, agricultural technology, and extension significantly affect motivation and performance. Likewise, motivation has a significant effect on farmer performance and is significant in mediating the influence of competence, agricultural technology, and extension on performance. Based on these findings, it is hoped that the Jayapura Regency Agriculture Service will be able to provide education to farmers in using agricultural technology so that the competence and motivation of cocoa farmers in the Jayapura Regency will increase.